Prognostic implications of novel beta cardiac myosin heavy chain gene mutations that cause familial hypertrophic cardiomyopathy. - Anan, R (1994)
Three novel beta cardiac myosin heavy chain (MHC) gene missense mutations, Phe513Cys, Gly716Arg, and Arg719Trp, which cause familial hypertrophic cardiomyopathy (FHC) are described. One mutation in exon 15 (Phe513Cys) does not alter the charge of the encoded amino acid, and affected family members have a near normal life expectancy. The Gly716Arg mutation (exon 19; charge change of +1) causes FHC in three family members, one of whom underwent transplantation for heart failure. The Arg719Trp mutation (exon 19; charge change of -1) was found in four unrelated FHC families with a high incidence of premature death and an average life expectancy in affected individuals of 38 yr. A comparable high frequency of disease-related deaths in four families with the Arg719Trp mutation suggests that this specific gene defect directly accounts for the observed malignant phenotype. Further, the significantly different life expectancies associated with the Arg719Trp vs. Phe513Cys mutation (P < 0.001) support the hypothesis that mutations which alter the charge of the encoded amino acid affect survival more significantly than those that produce a conservative amino acid change.